Teknik Elektro Berbasis Mikrokontroler - Wahid Najam; Taqiuddin Jayyid (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2023)
Various styles of decorative lights and forms of lighting will greatly influence the exoticism of the outside of the building, the presence of garden lights can be an option to create romance. Garden lights are an important element in creating an atmosphere that is not only beautiful, beautiful, but also full of high aesthetic value. Basically, garden lights not only play an important part in providing garden light or help provide lighting when walking in the garden at night and also provide a different atmosphere, especially adding lots of light points so that the spotlight will give a unique light image, thereby creating an atmosphere. around the park becomes beautiful and safe. Technological advances are increasingly rapid, making human life easier and more practical, one of these technological advances is microcontroller technology. The use of microcontrollers has recently expanded to all fields, its use is not only in the field of computers, but has also been used in other electronic equipment, for example devices that we see every day, such as cell phones, televisions, washing machines and even all the way to space instruments. The microcontroller itself is an electronic component which, when given input data, processes the input data, and then produces output from the processed data so that it can turn on the output on the microcontroller connected to the garden lamp.